Strategi Pemerintah Desa Dalam Peningkatan Ekonomi Masyarakat Melalui Program Pengurangan Pengangguran: Penelitian - Djuliandini; Nurmah; Akimudin; Malika Auliya Nurrin; Putri Yulianisa; Mohamad Imam Kamaludin (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to examine the strategy of Sindangheula Village Government, Pabuaran District, Pandeglang Regency, Banten, in improving community economy through unemployment reduction programs. The method used is descriptive qualitative with data collection techniques of observation, semi-structured interviews, and documentation. Research informants consisted of three groups: village officials (welfare division), business actors, and community members (youth/high school graduates). Data analysis used Miles and Huberman’s interactive model through data reduction, data presentation, and conclusion drawing. The results showed that the dominant livelihood in the village is the broom (sapu lidi) industry involving all layers of society, but it is still operated on a home-based scale with limited capital and marketing access. Village training programs such as Vocational Training Centers (BLK) and Package C education have existed but are not yet evenly distributed and had not been implemented in the current year. Unemployment is dominated by high school graduates who lack basic work skills. Synergy between village government, business actors, and the community is needed to optimize local potential to sustainably reduce unemployment rates. This is an open access article under the CC–BY-SA license.